Effect of plyometric training based on the integral reactive strength index of national-level jumpers and sprinters. a randomized crossover trial - Montoro-Bombú, R.; Sarmento, H.; Costa, A.; Pinheiro, V.; Malico Sousa, P.; Buzzichelli, C.; Rama, L. (Biology of Sport, 2026)
The Integral Reactive Strength Index (IRSI) has recently been described in the literature as a new indicator that normalizes the reactive strength index based on fall height. This study aimed to compare the effects of a plyometric training program based on IRSI versus a traditional jump training program on spatiotemporal variables associated with the performance of national-level jumpers and sprinters. A randomized, crossover trial with three parallel groups was conducted. Twenty-seven male track and field athletes were divided into three groups. The G-RT1 group consisting of 9 participants, began the experiment with IRSI based training as the load prescription criterion. The G-PT2 group consisting of 10 participants, started the experiment with traditional plyometric training, and the control group, G-CT3, consisting of 8 participants, continued its usual training. After 19 weeks, a two-way mixed analysis of variance for the G-RT1 group found a significant interaction and large effect sizes (ES) in the group-time relationship in the 60 m dash (p <- 0. 001; f = 101.2; n2 = 0.089), and the standing triple jump (STJ) (p <- 0.001; f = 119.8; n2 = 0.031). The G-PT2 also showed better results, but the ES was lower for the standing long jump (p <- 0.001; f = 52.7; n2 = 0.045), and the STJ (p <- 0.001; f = 22.7; np2 = 0.011). Meanwhile, the G-CT3 did not show significant improvement at the end of the program. It is concluded that the IRSI-based plyometric training program produces better results than the traditional program. The use of IRSI-based improves individualization, emphasizes high-intensity maintenance, and induces better results with less training volume.